Social Construction of Sexuality in Adolescents in the Digital Age: Implications for Risky Sexual Behavior and Its Impact on Reproductive Health - Cici Liska; Tri Arini Puspa Wati Manik; Ade Supriatna (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2026)
The digital era has transformed the way adolescents access information, including information about sexuality. Gadgets and social media have become primary agents of socialization, displacing the conventional roles of parents and schools. This phenomenon has shaped new and distinct understandings of sexual norms and behaviors among the younger generation. This study aims to analyze the social construction of sexuality among adolescents in the digital era and identify the digital factors that influence the formation of these concepts. This research used qualitative methods with a phenomenological approach. The results indicate that adolescents' understanding of sexuality is formed through three stages of sociological dialectics in cyberspace. The externalization process occurs when adolescents express their curiosity and bodily expression online through anonymous accounts to avoid real-world moral censorship. Next, objectification occurs through the work of timeline algorithms and online peer group validation, which institutionalize sexual narratives into objective reality and trigger the normalization of risky behaviors such as sexting and cyber-dating. Ultimately, at the internalization stage, these free and permissive cyber values ​​are fully absorbed into life principles and personal sexual identities. The digital era has structurally altered the landscape of adolescent sexual socialization by taking over the authority of traditional social control. The lack of adequate digital and sexual literacy filters ultimately gives rise to the phenomenon of dualism of consciousness, where adolescents physically live within conservative family rules, but mentally, their thinking has been completely constructed by the liberalization of digital values.